Ecological intensification measures to improve productivity and decrease nitrogen surplus in wheat-maize/watermelon intercropping system - Yanjie, Chen; Xiaotong, Yang; Yi, Zhang; Zhan, Xu; Cross, Paul; Chaochun, Zhang (International journal of sustainable development and world ecology, 2023)
Intercropping is a promising ecological intensification practice thanks to its improved crop yield and nutrient use efficiency compared with mono-cropping. However, there are constraints for achieving higher yields and efficiencies, and little is known about how to address such constraints. We conducted two experiments in a wheat-maize/watermelon intercropping study and examined the impacts of pollination services and cover crop addition on productivity and nitrogen (N) surplus, respectively. During the watermelon growing season, we investigated pollination services using three treatments (full cover, semi-cover, no cover) and evaluated fruit set rate, yield and pollination service index. During the maize growing season, we evaluated the impact of cover crop chicory (Cichorium intybus L.) on maize growth and soil residual inorganic N using three treatments (no cover crop, one row and two rows cover crop). Compared with the full cover treatment, semi-cover and no cover treatments increased the fruit set rate of watermelon by 42.95% and 73.85%, and fruit yield by 10.84 Mg·ha −1 and 11.48 Mg·ha −1 , respectively. Pollination services accounted for 57.5% of relative watermelon yield. Compared with the control (no cover crops), planting cover crops increased yield and N uptake of the maize while reducing the apparent N surplus by 25.9-26.0 kg·ha −1 . After the maize was harvested, inorganic N was largely distributed below the 60 cm soil depth. Providing pollination services and planting cover crops can be promising ecological intensification measures that improve productivity and decrease the N surplus of the intercropping system.